Configurationally Stable Chiral Dithia‐Bridged Hetero[4]helicene Radical Cation: Electronic Structure and Absolute Configuration. Issue 1 (5th December 2016) - Gliemann, Bettina D.; Petrovic, Ana G.; Zolnhofer, Eva M.; Dral, Pavlo O.; Hampel, Frank; Breitenbruch, Georg; Schulze, Philipp; Raghavan, Vijay; Meyer, Karsten; Polavarapu, Prasad L.; Berova, Nina; Kivala, Milan
Abstract: A stable chiral hetero[4]helicene radical cation was synthesized and characterized by UV/Vis absorption and EPR spectroscopy, as well as X‐ray crystallography. For the first time, a combination of chiroptical methods involving ECD, ORD, and VCD, supported by quantum mechanical predictions, enabled the elucidation of the absolute configuration of such open‐shell helical species. Abstract : Radically chiral : Stable chiral hetero[4]helicene radical cations were obtained and their absolute configurations were determined by a combination of chiroptical spectroscopy and quantum mechanical predictions.